2009
DOI: 10.1074/jbc.m809542200
|View full text |Cite
|
Sign up to set email alerts
|

Placenta-specific Methylation of the Vitamin D 24-Hydroxylase Gene

Abstract: Plasma concentrations of biologically active vitamin D (1,25-(OH)2D) are tightly controlled via feedback regulation of renal 1␣-hydroxylase (CYP27B1; positive) and 24-hydroxylase (CYP24A1; catabolic) enzymes. In pregnancy, this regulation is uncoupled, and 1,25-(OH) 2 D levels are significantly elevated, suggesting a role in pregnancy progression. Epigenetic regulation of CYP27B1 and CYP24A1 has previously been described in cell and animal models, and despite emerging evidence for a critical role of epigenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
86
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(93 citation statements)
references
References 82 publications
(66 reference statements)
5
86
0
2
Order By: Relevance
“…In normal human placenta and decidua from the first and second trimesters, expression of CYP27b1 and VDR is increased by more than 10-fold compared with endometrium, whereas the contrary is true for placental CYP24a1 expression (10). A recent study has demonstrated that CYP24a1 expression in the human placenta is downregulated by hypermethylation of its promoter (37). Increased maternal 1␣,25-(OH) 2 -D levels during pregnancy are not a consequence of increased PTH, which remains low during human and rodent pregnancy (24,38).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In normal human placenta and decidua from the first and second trimesters, expression of CYP27b1 and VDR is increased by more than 10-fold compared with endometrium, whereas the contrary is true for placental CYP24a1 expression (10). A recent study has demonstrated that CYP24a1 expression in the human placenta is downregulated by hypermethylation of its promoter (37). Increased maternal 1␣,25-(OH) 2 -D levels during pregnancy are not a consequence of increased PTH, which remains low during human and rodent pregnancy (24,38).…”
mentioning
confidence: 99%
“…calcitriol; CYP24a1; metabolism; kidney; placenta THE SECOSTEROID VITAMIN D has well-established classic effects on bone metabolism and mineral homeostasis (7,37). Vitamin D 3 (cholecalciferol) is generated from 7-dehydrocholesterol by a photolytic (UVB) conversion in the skin epidermis and from dietary animal sources, and vitamin D 2 (ergocalciferol) is obtained by dietary plant sources.…”
mentioning
confidence: 99%
“…No methylation was detected in any somatic human tissue tested. Methylation was also evident in marmoset and mouse placental tissue [9]. Epigenetics also plays important role.…”
Section: Introductionmentioning
confidence: 92%
“…Доказано, что плацента способна синтези-ровать 1,25(oH) 2 D. Существуют данные, кото-рые показывают, что производство плацентой 1,25(oH) 2 D в течение беременности на фоне увеличенного синтеза этого же витамина поч-ками превышает скорость выведения его из орга низма, способствуя его накоплению [58]. как следствие, у женщин в третьем триместре беременности содержание 1,25(oH) 2 D в сыво-ротке крови в два раза выше, чем у неберемен-ных или у женщин после родов [59,60].…”
Section: функции витамина D при беременностиunclassified